Plasma-enhanced protein patterning in a microfluidic compartmentalized platform for multi-organs-on-chip: a liver-tumor model. (7th June 2021) - Ferrari, Erika; Ugolini, Giovanni Stefano; Piutti, Claudia; Marzorati, Simona; Rasponi, Marco
Abstract: A microfluidic technique is presented for micropatterning protein domains and cell cultures within permanently bonded organs-on-chip devices. This method is based on the use of polydimethylsiloxane layers coupled with the plasma ablation technique for selective protein removal. We show how this technique can be employed to generate a multi-organ in vitro model directly within a microscale platform suitable for pharmacokinetic-based drug screening. We miniaturized a liver model based on micropatterned co-cultures in dual-compartment microfluidic devices. The cytotoxic effect of liver-metabolized Tegafur on colon cancer cell line was assessed using two microfluidic devices where microgrooves and valves systems are used to model drug diffusion between culture compartments. The platforms can reproduce the metabolism of Tegafur in the liver, thus killing colon cancer cells. The proposed plasma-enhanced microfluidic protein patterning method thus successfully combines the ability to generate precise cell micropatterning with the intrinsic advantages of microfluidics in cell biology.